1988
DOI: 10.1002/jlac.198819880902
|View full text |Cite
|
Sign up to set email alerts
|

Lactone, XX Phasentransfer‐Oxidation nach Grignardierung: Eine einfache Synthese δ,δ‐disubstituierter δ‐Lactone aus δ‐Valerolacton

Abstract: Durch eine Grinardierungs — Oxidations‐Sequenz, ohne Isolierung von Zwischenprodukten, läßt sich δ‐Valerolacton (4) sehr einfach in δ,δ‐disubstituierte δ‐Lactone 6 überführen. Genauer untersucht wurde der Reaktionsverlauf am Beispiel der Synthese von δ,δ‐Diphenyl‐δ‐valerolacton (6a) aus 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…2-(4-Cyclopropyl-4-hydroxy-4-phenylbutyl)-l,3-dioxolane (18a): t, = 17.05 min (A), R> = 0.61 (3/2); IR 3460 (OH), 3010, 1600,1480 (Ph), 1200,1030 , CHC-(OH)CH2(CH2)2), 1.85 (t, J = 7,2 H, CH2COH), 3. -3.9 (m, 4 H, 0CH2CH20), 4.6 (t, J = 5,1H, OCHO), 7.0-7.5 22.45,22.75, 26.3,27.8, 34.9,35.0,37.4,40.9,49.2,72.2,72.7,116.5, 135.65; MS 208 (M\ 1), 167 (61), 149 (100), 67 (46), 55 (30), 41 (44) NMR (300 MHz) 5 1.15-2.10 (m with a s at 1.56, all H); 18C NMR 16.8,21.75,22.0,26.05,30.25,31.55,34.5,36.9,41.25,66.7,75.45,123.15;MS 194 (M\ 2), 151 (38), 150 (100), 137 (98), 55 (39), 41 (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2-(4-Cyclopropyl-4-hydroxy-4-phenylbutyl)-l,3-dioxolane (18a): t, = 17.05 min (A), R> = 0.61 (3/2); IR 3460 (OH), 3010, 1600,1480 (Ph), 1200,1030 , CHC-(OH)CH2(CH2)2), 1.85 (t, J = 7,2 H, CH2COH), 3. -3.9 (m, 4 H, 0CH2CH20), 4.6 (t, J = 5,1H, OCHO), 7.0-7.5 22.45,22.75, 26.3,27.8, 34.9,35.0,37.4,40.9,49.2,72.2,72.7,116.5, 135.65; MS 208 (M\ 1), 167 (61), 149 (100), 67 (46), 55 (30), 41 (44) NMR (300 MHz) 5 1.15-2.10 (m with a s at 1.56, all H); 18C NMR 16.8,21.75,22.0,26.05,30.25,31.55,34.5,36.9,41.25,66.7,75.45,123.15;MS 194 (M\ 2), 151 (38), 150 (100), 137 (98), 55 (39), 41 (34).…”
Section: Discussionmentioning
confidence: 99%
“…2-[3-(l-HydroxycycIohexyl)propyl]-l,3-dioxolane (15a):46 tr = 13.74 min (A), Rf = 0.42 (3/2); IR 3420 (OH), 1120,1020 (CO) cm'1;NMR (60 MHz) 1.1-1.7 (m, 16 H, (CH2)3C(CH2)3), 2.15 (s, 1H, OH), 3.6-3.S (m,4 H, 0CH2CH20), 4.7 (t, J -5,1H, CH); MS 213 (M+ -1,1),153 (23), 101 (31), 73 (100), 45(38).2-[3-(l-Hydroxycyclooctyl)propyl]-l,3-dioxolane (16a)3), 3.6-3.85 (m,4 H, 0CH2CH20), 3.65 (t, J = 5,1 H, CH);MS 242 (M+, <1),181 (30), 127 (100), 101 (82), 96(46), 63 (62).…”
mentioning
confidence: 99%
“…We found that regiospecific monoalkylation of diols 2 by Merrifield resin is a simple, one-step approach to the synthesis of support bound tertiary alcohols that provides a range of carbon chain lengths between the linking functionality and the polymeric support (Scheme ). Thus, 6-methyl-1,6-heptanediol ( 2 , n = 5), 5-methyl-1,5-hexanediol ( 2 , n = 4), and 4-methyl-1,4-pentanediol ( 2 , n = 3) are prepared by the addition of excess MeLi to the appropriate lactone ( 1 , n = 5, 4, or 3), and 3-methyl-1,3-butanediol ( 2 , n = 2) is obtained commercially. Treatment of each diol with an equimolar amount of potassium tert -butoxide generates the corresponding monoalkoxides which are alkylated by Merrifield resin ( 3 ) to yield a series homologous solid-supported tert- alkyl alcohols ( 4 , n = 5, 4, 3, or 2).…”
Section: Resultsmentioning
confidence: 99%
“…In the former case, the starting benzophenone was recovered (run 7), although the reaction mixture turned red-purple and its 1 H NMR spectrum evidenced the generation of the dianion species. On the other hand, in the latter case, a color change (blue → red-purple → colorless) was observed, and a benzophenone-THF adduct, 1,1-diphenyl(pentane- d 8 )-1,5-diol, was isolated as the major product (run 8). The reaction seems to proceed through the formation of the lithium benzophenone dianion 4i,j,10 followed by its alkylative opening of THF- d 8 with the aid of a Lewis acidic lithium ion …”
mentioning
confidence: 97%